Tuft cell-like carcinomas: novel cancer subsets present in multiple organs sharing a unique gene expression signature$dmolecular diagnostics - Yamada, Yosuke; Bohnenberger, Hanibal; Kriegsmann, Mark; Kriegsmann, Katharina; Sinn, Peter; Goto, Norihiro; Nakanishi, Yuki; Seno, Hiroshi; Chigusa, Yoshitsugu; Fujimoto, Masakazu; Minamiguchi, Sachiko; Haga, Hironori; et al. (British journal of cancer, 2022)
Background: Tuft cells are chemosensory epithelial cells playing a role in innate immunity. Recent studies revealed cancers with a tuft cell-like gene expression signature in the thorax. We wondered whether this signature might also occur in extrathoracic cancers. Methods: We examined mRNA expression of tuft cell markers (POU2F3, GFI1B, TRPM5, SOX9, CHAT, and AVIL) in 19 different types of cancers in multiple extrathoracic organs with The Cancer Genome Atlas (TCGA) (N = 6322). Four different extrathoracic cancers in our local archives (N = 909) were analysed by immunohistochemistry. Results: Twenty-two (0.35%) extrathoracic tumours with co-expression of POU2F3 and other tuft cell markers were identified in various TCGA datasets. Twelve of the 22 “tuft cell-like tumours” shared poor differentiation and a gene expression pattern, including KIT, anti-apoptotic BCL2, and ionocyte-associated genes. In our archival cases, eleven (1.21%) tumours co-expressing POU2F3, KIT, and BCL2 on immunohistochemistry, i.e., were presumable tuft cell-like cancers. In three among five TCGA cohorts, the tuft cell-like cancer subsets expressed SLFN11, a promising biomarker of PARP inhibitor susceptibility. Conclusions: Tuft cell-like carcinomas form distinct subsets in cancers of many organs. It appears warranted to investigate their shared gene expression signature as a predictive biomarker for novel therapeutic strategies.
Gesehen am 31.07.2023